2020
DOI: 10.1182/hematology.2020006913
|View full text |Cite
|
Sign up to set email alerts
|

Management of AL amyloidosis in 2020

Abstract: In amyloid light chain (AL) amyloidosis, a small B-cell clone, most commonly a plasma cell clone, produces monoclonal light chains that exert organ toxicity and deposit in tissue in the form of amyloid fibrils. Organ involvement determines the clinical manifestations, but symptoms are usually recognized late. Patients with disease diagnosed at advanced stages, particularly when heart involvement is present, are at high risk of death within a few months. However, symptoms are always preceded by a detectable mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 40 publications
1
50
0
16
Order By: Relevance
“…Efficacy of vaccines against SARS-CoV-2 virus is of great importance to mitigate the Covid-19 pandemic. 1 The BNT162b2 mRNA vaccine (Comirnaty) is the first approved by both FDA and EMA, due to its efficacy in apparently healthy adults. 2 Recently, an assessment of the first vaccination dose effects among nursing facility residents and staff showed that there is some protection after the first injection.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of vaccines against SARS-CoV-2 virus is of great importance to mitigate the Covid-19 pandemic. 1 The BNT162b2 mRNA vaccine (Comirnaty) is the first approved by both FDA and EMA, due to its efficacy in apparently healthy adults. 2 Recently, an assessment of the first vaccination dose effects among nursing facility residents and staff showed that there is some protection after the first injection.…”
Section: Supporting Informationmentioning
confidence: 99%
“…To the Editor: Daratumumab/dexamethasone (DD) or daratumumab/bortezomib/ dexamethasone (DVD) have become standard salvage regimens in systemic light-chain amyloidosis (AL). 1 Excellent results have been achieved with the combination of daratumumab/lenalidomide/dexamethasone (DRD) in relapsed/refractory and newly diagnosed multiple myeloma (MM). 2 However, in AL the efficacy and toxicity of DRD has not yet been separately assessed.…”
mentioning
confidence: 99%
“…Approximately 20% of AL amyloidosis patients have advanced cardiac involvement at diagnosis (stage IIIb), and treatment of these patients remains an unmet need. Ideally, these patients need a very rapidly acting, safe regimen 93 . The safety profile and rapidity of action of subcutaneous daratumumab make this agent very appealing in this setting, and a phase II trial is currently ongoing (NCT04131309).…”
Section: Advances In the Treatment Of Cardiac Amyloidosismentioning
confidence: 99%
“…Other potential but infrequent signs of organ involvement due to amyloid fibrils include hepatomegaly with cholestasis, postural hypotension, syncope, peripheral neuropathy (as ascending, symmetric, small fibers/axonal), gastrointestinal mobility alterations, unintended weight loss, periorbital purpura (i.e., "raccoon eyes"), macroglossia and swelling of the submandibular salivary glands and the shoulder (i.e., "shoulder pad" signs). 8 In symptomatic patients, immunofixation of serum and urine and measurement of FLC have to be performed to check for the presence of monoclonal gammopathy. If a monoclonal protein is present, tissue diagnostic for AL amyloidosis has to be carried out.…”
Section: Systemic Al Amyloidosis and Precision Medicinementioning
confidence: 99%
“…If a monoclonal protein is absent in patients with suspected cardiac amyloidosis, a cardiac scintigraphybased diagnostic pathway with bone tracers is recommended, to look for transthyretin (ATTR) amyloidosis. 8 Molecular genetic analysis is necessary to differentiate between hereditary (rare) and wild-type (frequent) ATTR amyloidosis.…”
Section: Systemic Al Amyloidosis and Precision Medicinementioning
confidence: 99%